Framework for Product Anti-Counterfeiting using Blockchain Technology - William, P.; Jadhav, Dushyant; Cholke, Pratik; Jawale, M. A.; Pawar, A.B. (2022 International Conference on Sustainable Computing and Data Communication Systems (ICSCDS), 2022)
In recent years, blockchain technology has gained more attention, and a plethora of applications have developed. It's a digital money. In addition to solving the problem of double-spending, Bitcoin is a well-known Blockchain application since it does it without relying on a central authority. Blockchain technology provides a tamper-proof basis for any application that relies on it. With this article's help, shoppers will no longer be solely reliant on merchants to verify the legitimacy of things. We present a decentralised Blockchain system for anti-counterfeiting items. This system enables producers to deliver authentic products without managing direct-operated storefronts, considerably lowering the cost of product quality assurance.